CIENCIA ergo sum: una experiencia editorial - Loría, Eduardo; Pérez, José Manuel; Paredes, Javier; Brito, Luis (CIENCIA ergo-sum; Vol. 6 Núm. 3 (1999): CIENCIA ergo-sum (noviembre 1999-febrero 2000), 2017)
-